2016
DOI: 10.1590/s0080-623420160000500015
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork in nursing: restricted to nursing professionals or an interprofessional collaboration?

Abstract: Objective:To understand the nursing professionals' conceptions of teamwork and their elements. Method: A qualitative study conducted in an oncological hospital using a semistructured interview with 21 nursing professionals. Results: Two conceptions emerged from the accounts: teamwork restricted to nursing professionals and teamwork with interprofessional collaboration with particular importance for interactive dimensions: communication, trust and professional bonds, mutual respect and recognition of the other'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
47

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 17 publications
1
19
0
47
Order By: Relevance
“…A study with Australian nurses who self-perceived themselves as resilient, identified the importance of teamwork as one of the main motivators in the work environment, configuring itself as a coping strategy in the face of adversity at work (22) . Regarding teamwork in nursing, it is worth noting that sharing decision-making processes enhances co-responsibility between nurses and nursing technicians, which can favor communication and avoid conflicts in the work environment (23) . As a negative aspect of the work, the participants highlighted the prejudice induced by people in their own social life as a result of their professional performance in a psychiatric hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A study with Australian nurses who self-perceived themselves as resilient, identified the importance of teamwork as one of the main motivators in the work environment, configuring itself as a coping strategy in the face of adversity at work (22) . Regarding teamwork in nursing, it is worth noting that sharing decision-making processes enhances co-responsibility between nurses and nursing technicians, which can favor communication and avoid conflicts in the work environment (23) . As a negative aspect of the work, the participants highlighted the prejudice induced by people in their own social life as a result of their professional performance in a psychiatric hospital.…”
Section: Discussionmentioning
confidence: 99%
“…O trabalho em equipe consiste em uma modalidade de trabalho coletivo que se configura na relação recíproca entre as múltiplas intervenções técnicas e a interação dos agentes de diferentes áreas profissionais, por meio das conexões que existem entre as diferentes atividades executadas (14) . Houve discussão sobre o trabalho em equipe nos cursos de graduação, de acordo com os participantes.…”
Section: Atuação Da Equipe De Saúde E a Inclusão Do Paciente Como Parunclassified
“…11 Isso porque não existe ação humana sem comunicação dialógica e, quando essa comunicação é horizontal, em que os sujeitos sociais compartilham experiências, há transformação e autotransformação. 12 Isso ocorre pelo fato de o homem estar situado em sua cultura e na sociedade a que pertence e, desse modo, sua consciência não é vazia, mas condicionada pelo âmbito em que este está inserido. 13 Na mesma medida, refletir sobre uma realidade tem o potencial de redirecionar um fazer profissional.…”
Section: […] Agora Quase Todos Carregam Junto a Luva (Vs)unclassified